Aerobic And Anaerobic Capacity Analysis Of Rowing Rowers Using Wattbike And Rowing Ergometer Concept II - Alfy Fauzia Azmi; Amung Ma’mun; Boyke Mulyana (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
The purpose of this study was to determine "whether there is a comparison of aerobic and anaerobic capacities using a stationary and rowing bicycle ergometer". The research method used is a descriptive method with a purposive sampling technique, namely 10 athletes rowing training athletes in the city of Bandung, with the criteria for determining the sample are rowing athletes of the female gender. The research instruments used were a modified Wingate rowing ergometer test (WanTr) performed on a Concept II rowing machine (Vermont, USA) and a 30-second "all-out" WAnTr test on a cycling ergometer to determine the athlete's anaerobic capacity. This finding is following the assumptions formulated, namely that there are differences in the results of aerobic and anaerobic tests using an ergometer rowing machine and a Wingate test (watt bike). shows the results of the independent samples test output between the aerobic ergo rowing and the aerobic Wingate test, it is known that the t value is 0.171 and the Sig. (2-tailed) value is 0.888 which is greater than 0.05. it can be concluded that there is a comparison of aerobic and anaerobic capacity using the rowing ergometer and Wingate test